Fluoride content in bottled waters, juices and carbonated soft drinks in Mexico City, Mexico - M. D. JIMÃƒÆ’Ã¢â‚¬Â°NEZ-FARFÃƒÆ’Ã‚ÂN, J. C. HERNÃƒÆ’Ã‚ÂNDEZ-GUERRERO, J. P. LOYOLA-RODRÃƒÆ’Ã‚ÂGUE (Paediatric Dentistry, 2004)
The objective of this study was to analyse 283 samples of soft drinks available in the metropolitan market of Mexico City, Mexico: 105 juices, 101 nectars, 57 carbonated drinks and 20 bottled waters.